2021
DOI: 10.1115/1.4050769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sodium boiling models using KNS-37 LOF experiments

Abstract: The computational codes used in the evaluation of the ESFR-SMART reactor performance and specifically their sodium boiling models are assessed using two KNS-37 LOF experiments, i.e. L22 and L29 tests, where boiling onset and two-phase flow regime up to dry-out occurred. The well-equipped KNS-37 experimental facility provided very valuable information for understanding the physical phenomena occurring in a 37-pin subassembly under LOF conditions, as well as experimental data to be used for computational tools v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Reactor based on open publications [6,7]. -A computational exercise on sodium boiling modelling was conducted based on a KNS-37 sodium loop experiment featuring sodium boiling in pin-bundle geometries [8].…”
Section: Benchmarking Of Codesmentioning
confidence: 99%
“…Reactor based on open publications [6,7]. -A computational exercise on sodium boiling modelling was conducted based on a KNS-37 sodium loop experiment featuring sodium boiling in pin-bundle geometries [8].…”
Section: Benchmarking Of Codesmentioning
confidence: 99%
“…A validation has been performed in (Chenu, 2011) on incorporated sodium boiling model in TRACE considering annular flow as the dominant regime up to dryout and a smooth breakdown of the liquid film after dryout onset. Recently, validation of the models was performed using the KNS-37 sodium boiling experiment, which has been reported in (Perez-Martin et al, 2022).…”
Section: The Computational Toolmentioning
confidence: 99%
“…In this study, the specific sodium boiling modeling aspects included in TRACE by PSI have not been evaluated but rather emphasis was given to analyze the specific behavior of the ESFR-SMART core design. This is because such study has been performed in (Perez-Martin et al, 2022), based on the validation exercise of TRACE with a ULOF sodium boiling experiment.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…A review of the history of experiments for sodium fast reactors revealed that most of them were dedicated to one topic to answer special question of investigation of phenomenology or deliver data for system codes, especially for thermal hydraulics [1]. At KIT, a huge amount of data has been gathered and have been made partially available for the European projects JASMIN [2] and ESFR-SMART [6]. Today, the ongoing evolution of computer and codes, especially CFD codes, require more data with higher local and temporal resolution.…”
Section: Introduction 1 Introductionmentioning
confidence: 99%